Assessing terrestrial water storage anomalies uncertainties in south america using the three-cornered hat method - MELO, Marcella Fernandes de Oliveira (2023)
The GRACE mission (Gravity Recovery and Climate Experiment) and its successor, the GRACE Follow-On (GRACE-FO) have been monitoring the terrestrial water storage anomalies (TWSA) since April 2002. The Space Research Center (CSR), Jet Propulsion Laboratory (JPL), and Goddard Space Flights (GSFC) are operationally providing individual monthly solutions based on the mass concentration (mascon) solution as the radial basis function. The inverted TWSA maps (or regional averaged values) from these centers are being used in many applications. However, as terrestrial data are unavailable, the uncertainties and their confidence intervals are unknown. Consequently, this work aims to evaluate the quality of each TWSA solution from the three processing centers using a generalized formulation of the three-cornered hat method (TCH) and estimate the respective confidence intervals for the uncertainties. Overall, the TCH results for the study period from April 2002 to June 2017 over South America indicate that the uncertainties of TWSA from CSR, JPL, and GSFC are 34.4, 47.4, and 38.7 mm, respectively. At basin scale, the good performance of the TWSA based on CSR mascon solution is observed. The THC-based results agree with an ensemble mean from the three solutions. Regarding the confidence intervals, in general, the reliability of the data decreases as the area decreases. In this sense, this study supports hydrologists in selecting the best TWSA solution for hydrological studies.